2016
DOI: 10.1007/s10162-016-0559-7
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Tilt Perception During Centrifugation in Patients with Vestibular Migraine

Abstract: Vestibular migraine (VM), defined as vestibular symptoms caused by migraine mechanisms, is very common but poorly understood. Because dizziness is often provoked in VM patients when the semicircular canals and otolith organs are stimulated concurrently (e.g., tilting the head relative to gravity), we measured tilt perception and eye movements in patients with VM and in migraine and normal control subjects during fixed-radius centrifugation, a paradigm that simultaneously modulates afferent signals from the sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…Vestibular migraine patients exhibited elevated vestibular-ocular and perceptual thresholds during yaw (horizontal plane) rotations. This is in concordance with a previous finding that illustrated elevated thresholds for tilt perception during fixed-radius centrifugation in vestibular migraine patients (Wang and Lewis, 2016). Contrastingly, a separate study revealed that during dynamic roll tilt (frontal plane), vestibular migraine patients’ exhibit decreased perceptual thresholds (i.e.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Vestibular migraine patients exhibited elevated vestibular-ocular and perceptual thresholds during yaw (horizontal plane) rotations. This is in concordance with a previous finding that illustrated elevated thresholds for tilt perception during fixed-radius centrifugation in vestibular migraine patients (Wang and Lewis, 2016). Contrastingly, a separate study revealed that during dynamic roll tilt (frontal plane), vestibular migraine patients’ exhibit decreased perceptual thresholds (i.e.…”
Section: Discussionsupporting
confidence: 94%
“…Despite the pathophysiology of vestibular migraine remaining largely unknown, recent findings have provided some preliminary insights. These include reports of abnormal vestibular thresholds during tilt (Lewis et al , 2011; Wang and Lewis, 2016) and abnormal cortical interactions between visual and vestibular networks. The evidence for this latter point is provided by a neuroimaging study, which revealed altered metabolic activity in visual and vestibular cortical areas in two patients imaged during an acute episode of vestibular migraine (Shin et al , 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Reorienting the head relative to gravity modulates activity in the semicircular canals, which encode angular head velocity, and otolith organs, which encode gravity and linear acceleration. Based on these observations, we proposed that central integration of canal and otolith signals is abnormal in VM, a hypothesis supported by our recent psychophysical studies (Lewis et al 2011a(Lewis et al , 2011bWang and Lewis 2016).…”
supporting
confidence: 55%
“…Further evidence that VM is a disease of multisensory integration in the central nervous system was seen in a study of tilt perception in VM, migraine, and normal patients. When the 3 groups of patients sat in a centrifuge and an interaural centrifugal force was generated, the development of the perception of tilt in the roll plane was slower in the VM group compared to the other 2, but eye movement responses such as rotational axis shift were the same in all groups [ 46 ]. In other roll-type experiments, VM patients were found to have decreased motion perception thresholds when canal and otolith signals were presented simultaneously, but perception of tilt was slower when the signals were conflicting [ 47 ].…”
Section: Reviewmentioning
confidence: 99%
“…This may be a potential origin for motion sensitivity in VM patients. The authors believe that these results suggest VM is, at least in part, a result of dysfunctional vestibular signal integration and abnormal sensitization possibly of cerebellar origin [ 46 , 47 ].…”
Section: Reviewmentioning
confidence: 99%